2018
DOI: 10.1016/j.kjms.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐treatment with proton pump inhibitors decreases the success of primary Helicobacter pylori eradication using a vonoprazan‐based regimen

Abstract: Vonoprazan-based regimens have improved the rate of successful Helicobacter pylori (H. pylori) eradication, but it has not reached 100%. The aim of this study is to clarify significant predictors of successful H. pylori eradication using a vonoprazan-based regimen. In this retrospective cohort study, 174 patients who underwent primary H. pylori eradication therapy were included. All patients underwent esophagogastroduodenoscopy before treatment. The vonoprazan-based regimen includes amoxicillin 750 mg, clarith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Second, VA‐dual may be less affected by common use or concomitant drugs. Shinozaki et alreported that pre‐treatment with PPI decreases the eradication rate when VAC‐triple is used 12 . In contrast, in the present study, the use of PPIs before eradication therapy did not affect the eradication rate of VA‐dual.…”
Section: Discussioncontrasting
confidence: 79%
“…Second, VA‐dual may be less affected by common use or concomitant drugs. Shinozaki et alreported that pre‐treatment with PPI decreases the eradication rate when VAC‐triple is used 12 . In contrast, in the present study, the use of PPIs before eradication therapy did not affect the eradication rate of VA‐dual.…”
Section: Discussioncontrasting
confidence: 79%
“…In recent years, several studies have compared eradication rates between VPZ-containing and PPI-containing triple therapies across centers in Japan. As shown in Table 2, up until September 2018, 23 reports had investigated the efficacy of first-line VPZ-containing therapy (21 reports for VPZ/AMX/CLR and 2 reports for VPZ/MNZ/CLR) (Matsumoto et al, 2016; Murakami et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016, 2018; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Katayama et al, 2017; Maruyama et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b, 2018a; Sugimoto et al, 2017; Tanabe et al, 2017, 2018; Mori et al, 2018; Ozaki et al, 2018), and 19 reports had compared the efficacy between VPZ-containing therapy and PPI-containing therapy, including 3 randomized control trials (Murakami et al, 2016; Maruyama et al, 2017; Sue et al, 2018a) and 16 non-randomized retrospective cohort trials (Matsumoto et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b; Mori et al, 2018; Ozaki et al, 2018; Tanabe et al, 2018).…”
Section: First-line Vonoprazan-containing Eradication Therapymentioning
confidence: 99%
“…As shown in Table 2, first-line triple VPZ-containing therapies (VPZ/AMX/CLR) therefore show superior efficacy in Japanese individuals in terms of H. pylori eradication compared to PPI-containing therapies (Matsumoto et al, 2016; Murakami et al, 2016; Noda et al, 2016; Shichijo et al, 2016; Shinozaki et al, 2016, 2018; Suzuki et al, 2016; Tsujimae et al, 2016; Yamada et al, 2016; Kajihara et al, 2017; Katayama et al, 2017; Maruyama et al, 2017; Nishizawa et al, 2017; Ono et al, 2017; Sakurai et al, 2017; Sue et al, 2017a,b, 2018a; Sugimoto et al, 2017; Tanabe et al, 2017, 2018; Mori et al, 2018; Ozaki et al, 2018). According to a grading system established by Graham et al (2007) the 69.1–75.0% eradication rate of PPI-containing therapies constitutes an unacceptable grade (grade F).…”
Section: First-line Vonoprazan-containing Eradication Therapymentioning
confidence: 99%
“…All patients underwent esophagogastroduodenoscopy prior to eradication therapy. H. pylori infection status was confirmed by a rapid urease test, stool antigen test, histology, serum IgG, or 13 C-urea breath test (UBT). The degree of gastric atrophy was classified based on the Kimura-Takemoto classification [11].…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included missing data (height, weight, or endoscopic findings), pre-treatment with a PPI or H2RA, firstline eradication therapy with a PCAB-based regimen, or a history of distal gastrectomy. Since we recently reported that PPI and H2RA decreased the success of H. pylori eradication [13], patients previously treated with PPI or H2RA were excluded from this study to eliminate a possible source of bias. All patients who underwent PPI-based second-line therapy had not undergone PCAB-based first-line therapy.…”
Section: Second-line H Pylori Eradication Regimen and Treatment Outcomementioning
confidence: 99%